On the Use of a Non-Constant Non-Affine or Slip Parameter in Polymer Rheology Constitutive Modeling - Nikiforidis, Vasileios-Martin; Tsalikis, Dimitrios G.; Stephanou, Pavlos S. (My University, 2022)
Since its introduction in the late 1970s, the non-affine or slip parameter, ξ , has been routinely employed by numerous constitutive models as a constant parameter. However, the evidence seems to imply that it should be a function of polymer deformation. In the present work, we phenomenologically modify a constitutive model for the rheology of unentangled polymer melts [P. S. Stephanou et al. J. Rheol. 53, 309 (2009)] to account for a non-constant slip parameter. The revised model predictions are compared against newly accumulated rheological data for a C48 polyethylene melt obtained via direct non-equilibrium molecular dynamics simulations in shear. We find that the conformation tensor data are very well predicted; however, the predictions of the material functions are noted to deviate from the NEMD data, especially at large shear rates.
Keywords: Unentangled systems; Constitutive modeling; Materials functions; Non-affine parameter; Slip parameter; Conformation tensor; NEMD simulations; Atomistic simulations; Polyethylene